2022
DOI: 10.31616/asj.2021.0015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Continuous Infusion of Dexmedetomidine or a Subanesthetic Dose Ketamine on Transcranial Electrical Motor Evoked Potentials in Adult Patients Undergoing Elective Spine Surgery under Total Intravenous Anesthesia: A Randomized Controlled Exploratory Study

Abstract: Purpose: To compare effects of dexmedetomidine or a subanesthetic dose of ketamine on the amplitude and latency of transcranial electrically generated motor evoked potentials. Overview of Literature: Total intravenous anesthesia (TIVA) is a standard anesthesia technique for transcranial electrical motor evoked potential monitoring in spine surgery. We aimed to determine whether the use of dexmedetomidine and ketamine as a component of TIVA exerted any beneficial effect on the quality of monitoring. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Chakrabarti et al [ 33 ] reported similar findings in patients undergoing cerebellopontine angle surgeries with TIVA when dexmedetomidine was used as an adjuvant. Andleeb et al [ 16 ] compared various adjuvants (ketamine, dexmedetomidine, normal saline) in patients requiring TIVA with IONM and found a significant reduction in propofol consumption in the dexmedetomidine group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chakrabarti et al [ 33 ] reported similar findings in patients undergoing cerebellopontine angle surgeries with TIVA when dexmedetomidine was used as an adjuvant. Andleeb et al [ 16 ] compared various adjuvants (ketamine, dexmedetomidine, normal saline) in patients requiring TIVA with IONM and found a significant reduction in propofol consumption in the dexmedetomidine group.…”
Section: Discussionmentioning
confidence: 99%
“…They found no significant changes in amplitude and latency in intergroup and intragroup analysis. Andleeb et al [ 16 ] demonstrated that the baseline median amplitude was comparable in three groups receiving dexmedetomidine, ketamine, and saline. At 60 minutes and at the end of the surgery, there was an increase in the amplitude of MEP in the ketamine group and dexmedetomidine group (significantly higher in the ketamine group) with no changes in the latencies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations